The relation between nonspecific hyperreactivity of the airways and atopic constitution in asthmatics - Novković, Dobrivoje; Petrović, Marina; Živkovic, Vladan; Baletić, Nenad (Vojnosanitetski pregled, 2017)
Background/Aim. Hyperreactivity of the airways caused by inflammation in asthmatics is the most important pathophysiological change. It represents a suitable ground that in the presence of risk factors and the drivers of asthma, asthmatic attack occurs. Atopic constitution is one of the most important risk factors for the development and expression of asthma. The aim of our study was to investigate the relationship between nonspecific airway hyperreactivity and atopic constituton in asthmatics. Methods. This retrospective analysis was conducted considering the results of nonspecific bronchoprovocative test with histamine, skin tests to inhalant allergens and total IgE levels in the serum of asthmatic patients with controlled bronchial asthma. The sample consisted of 162 asthmatics examined during one-year period. Results. The examinees were male asthmatic patients, aged between 18 and 30 years. We found that the examinees with a pronounced non-specific hyperreactivity had more significant skin reaction to inhaled allergens and higher levels of total IgE in serum. Conclusion. The results of our study show that the intensity of airway hyperresponsiveness to histamine in asthmatics is directly related to atopic constitution.
Keywords: asthma; respiratory hypersensitivity; immunoglobulin e; hypersensitivity; immediate; histamine; skin test